Severe reversible cardiomyopathy associated with adrenal crisis caused by isolated adrenocorticotropin deficiency: a case report - Li Wang; Fangfang Bu; Lanjie He; Guihua Yao; Guihua Yao (Frontiers in Cardiovascular Medicine)
Adrenal crisis, also known as acute adrenal insufficiency, is an endocrine emergency that is associated with high mortality rates. Reversible cardiomyopathy with severe heart failure is a rare complication of adrenal crisis. Isolated adrenocorticotropin deficiency (IAD) is a rare condition of pituitary adrenal insufficiency. In this case report, we describe a 74-year-old male patient who was in good physical health and was admitted to our hospital with a sudden onset of fever and confusion that was complicated by hyponatremia and hypotension. Cardiac ultrasound showed significantly reduced left ventricular ejection fraction (LVEF; 10%). The patients was initially diagnosed with “septic shock” because of elevated inflammatory indicators and treated with mechanical circulatory support, antibiotics, fluid resuscitation, and intravenous administration of 50 mg hydrocortisone every 6 h for 2 days (400 mg in total). The symptoms of the patient improved significantly by this treatment in 6 days. The LVEF improved from 10% to 40%. However, the initial treatment did not alleviate hypotension and confusion. Therefore, the status of adrenal function was analyzed using blood and urine cortisol tests. Blood and urinary cortisol levels were significantly reduced, but concurrent increase in the ACTH levels were not observed. This indicated adrenal crisis. Subsequently, the patient was initially administered intravenous injection of hydrocortisone (50–150 mg/day) for 5 days, and then transitioned to a physiological supplement dose orally. The LVEF value improved further to 52%. Finally, the patient was diagnosed with adult isolated ACTH deficiency. The patient was prescribed regular oral hydrocortisone. The patient has not shown any signs of heart failure during follow up for more than half a year. In summary, we described a rare and severe case of adrenal crisis complicated with reversible cardiomyopathy that was caused by isolated ACTH deficiency. In such a case, conventional guideline directed medical therapy (GDMT) for heart failure was not considered suitable because of the underlying hypotension, hypoglycemia, and hyponatremia. Our study showed that timely supplementation of glucocorticoids achieved better therapeutic effects in patients with adrenal crises complicated by severe cardiomyopathy.